Do we need them? When immigrant communities are perceived as indispensable to national identity or functioning of the host society - Guerra, R.; Gaertner, S. L.; António, R.; Deegan, M. (European Journal of Social Psychology, 2015)
This study proposed a new perspective to look at the consequences of the formation of immigrant communities in globalized societies, by investigating the impact of two forms of group indispensability on majority attitudes towards immigrants. Specifically, it explored whether perceived indispensability of different immigrant groups to the national identity and their contributions to the functioning of the host society are related to the development of more positive attitudes towards them. We also explored whether such effects would be mediated by the inclusion of immigrants within the national common identity and whether these effects would be stronger among host country members with a stronger civic than ethnic conception of national citizenship. Results supported these predictions among a sample of native Portuguese citizens (N=118). As predicted, these effects were driven by perceptions of different types of indispensability for three immigrant groups in Portugal, who differed in their historical relations with the host society.